2020
DOI: 10.1111/tpj.15045
|View full text |Cite
|
Sign up to set email alerts
|

A restorer‐of‐fertility‐like pentatricopeptide repeat protein promotes cytoplasmic male sterility in Arabidopsis thaliana

Abstract: SummaryPentatricopeptide repeat (PPR) proteins form a large family of proteins targeted to organelles, where they post‐transcriptionally modulate gene expression through binding to specific RNA sequences. Among them, the mitochondria‐targeted restorer‐of‐fertility (Rf) PPRs inhibit peculiar mitochondrial genes that are detrimental to male gametes and cause cytoplasmic male sterility (CMS). Here, we revealed three nuclear loci involved in CMS in a cross between two distant Arabidopsis thaliana strains, Sha and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…The location of the Rf loci found in previous cases of CMS involving the Sha accession partially overlap with those reported in our study (Simon et al, 2016;Durand et al, 2020). The degree of fertility described for CMS found in the Sha x Mr-0 interaction, resulted from a complex interplay between nuclear segregation distorter (pollen killer) loci and several Rf loci (Simon et al, 2016).…”
Section: Identification Of Rf Locisupporting
confidence: 81%
See 2 more Smart Citations
“…The location of the Rf loci found in previous cases of CMS involving the Sha accession partially overlap with those reported in our study (Simon et al, 2016;Durand et al, 2020). The degree of fertility described for CMS found in the Sha x Mr-0 interaction, resulted from a complex interplay between nuclear segregation distorter (pollen killer) loci and several Rf loci (Simon et al, 2016).…”
Section: Identification Of Rf Locisupporting
confidence: 81%
“…The degree of fertility described for CMS found in the Sha x Mr-0 interaction, resulted from a complex interplay between nuclear segregation distorter (pollen killer) loci and several Rf loci (Simon et al, 2016). The three strongest of these Rf loci (named L1, L3 and L5) were also found in the analysis of the Sha x Cvi-0 CMS (Durand et al, 2020).…”
Section: Identification Of Rf Locimentioning
confidence: 94%
See 1 more Smart Citation
“…Observations were made using a Zeiss Axio Imager2 microscope and photographs were taken using an AxioCam MRm (Zeiss) camera. Propidium iodide and Alexander staining (Alexander 1969) of pollen were performed as described in Durand et al (2021).…”
Section: Cytological Analysesmentioning
confidence: 99%
“…For example, MutS HOMOLOG1 (MSH1) affects fertility reversion from cytoplasmic male sterility in Brassica juncea ( Zhao et al, 2021b ). The RFL24 protein in Arabidopsis thaliana is a mitochondrial-targeted pentatricopeptide repeat that can inhibit mitochondrial genes related to male gametes to cause cytoplasmic male sterility ( Durand et al, 2021 ). A recent study found that Rf1 and Rf3 candidates in hybrid wheat can bind to the mitochondrial orf279 transcript and induce its cleavage to prevent the expression of cytoplasmic male sterility, thereby restoring normal pollen production in transgenic wheat plants ( Geyer et al, 2016 ; Melonek et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%